Anti-inflammatory and analgesic activities of the ethanolic extract of Seaweed Asparagopsis spp. Isolated from the Bay of Bengal, Bangladesh - Nayem, Abu; Akter, Maksuda; Chowdhury, Khadiza Rezwana; Alim, Md Abdul; Zaman, Nazia Rifat; Hossain, Mohammad Nazir (Bioresearch Communications, 2024)
The marine zone of Bangladesh covers a great diversity of natural ecosystems including a marine environment rich in commercially important seaweeds. Seaweeds are widely used in the pharmaceutical, cosmetics, chemical, antibacterial, and food industries globally. According to the Food and Agriculture Organization of the United Nations (FAO), China, Indonesia, Korea, the Philippines, and Japan are the top five nations in the world for seaweed production. In recent times, Bangladesh has initiated comprehensive research endeavours focused on seaweed, recognizing its immense potential across diverse sectors. Seaweed in Bangladesh is primarily harvested for various purposes, including food, medicine, and industrial applications. In this study, red seaweed Asparagopsis collected from the coast of Saint Martin’s island of the Bay of Bengal was tested for its bioactive properties like anti-inflammatory and analgesic activity. Anti-inflammatory test was done using carrageenan suspension and three analgesic tests e.g. hot plate test, acetic acid-induced writhing test, and formic acid-induced test were performed in mice model in the laboratory with 50% ethanol extract of Asparagopsis. Following in vivo testing, no significant activity was observed. However, Asparagopsis was found to be rich in phytochemicals like phenols, flavonoids, saponin, glycoside, steroids, tannins, and alkaloids suggesting its importance for future scientific study. This may create a door to a new world in the Blue Economy sector of Bangladesh. Bioresearch Commu. 10(2): 1583-1591, 2024 (July)